PENERAPAN MODEL INKUIRI TERBIMBING DALAM MENINGKATKAN MOTIVASI BELAJAR DAN PENGUASAAN KONSEP SISWA - Siti Nur Halimah; Ratu Betta Rudibyani; Tasviri Efkar (Universitas Lampung, 2015)
The pre-experiment research with one group pretest-posttest design had been done to describe the effectiveness of guided inquiry learning model in improving students learning and concept mastery. This research was conducted in SMAN 1 Natar for 2015/2016 academic year with the 10th grade-8 as sample class which it was obtained by using cluster random sampling technique. Guided inquiry learning model effectiveness was determined by t test and the effect size test of the differences between the mean value of n-Gain both students learning motivation and concept mastery. The research result showed that guided inquiry learning model was effective in improving students learning motivation and concept mastery students. Penelitian pre-eksperimen dengan One Group Pretest-Posttest Designtelah dilakukanuntuk mendeskripsikan efektivitas model inkuiri terbimbing dalam meningkatkan motivasi belajar siswa dan penguasaan konsep siswa. Penelitian ini dilakukan di SMAN 1 Natar tahun akademik 2015/2016 dengan kelas X-8 sebagai sampel yang diperoleh dengan menggunakan teknik cluster random sampling. Efektivitas model inkuiri terbimbing ditentukan dengan uji t dan uji effect size terhadap perbedaan rerata nilai n-Gain motivasi belajar dan penguasaan konsep siswa. Hasil penelitian menunjukkan bahwa model inkuiri terbimbing efektif dalam meningkatkan motivasi belajar dan penguasaan konsep siswa.Kata kunci: inkuiri terbimbing, motivasi belajar, penguasaan konsep